PENGARUH PENGETAHUAN AKUNTANSI DAN KEPRIBADIAN WIRAUSAHA TERHADAP KINERJA MANAJERIAL (Studi pada UMKM Batik Tulis Kabupaten Probolinggo) - Ferina Firdayanti; Nur Diana; Junaidi Junaidi (Universitas Islam Malang, 2020)
ABSTRACTThe purpose of this study was to determine the effect of accounting knowledge and entrepreneurial personality on managerial performance. The population in this study was the Batik UMKM in Probolinggo District. “The sample selected using purposive sampling and obtained as many as 108 respondents. based on established criteria. This research uses multiple linear regression models. The results of this study indicate that” accounting knowledge and entrepreneurial personality affect managerial performance. Accounting knowledge has a positive effect on managerial performance. Entrepreneurial personality has a positive effect on managerial performance.Keywords : Accounting knowledge, entrepreneurial personality, and managerial performance